Casinos, Crime, and Community Costs - Grinols, Earl L.; Mustard, David B. (The Review of Economics and Statistics, 2006)
We examine the relationship between casinos and crime using county-level data for the US between 1977 and 1996. Casinos were non-existent outside Nevada before 1978, and expanded to many other states during our sample period. Most factors that reduce crime occur before or shortly after a casino opens, while those that increase crime, including problem and pathological gambling, occur over time. The results suggest that the effect on crime is low shortly after a casino opens, and grows over time. Roughly 8 percent of crime in casino counties in 1996 was attributable to casinos, costing the average adult $75 per adult per year.